Perfil clínico e laboratorial dos pacientes com fibrose cística no Espírito Santo : a dosagem do cloreto correlacionou inversamente ao valor da elastase pancreática fecal - Melotti, Roberta de Cássia Nunes Cruz (2018)
The Cystic Fibrosis is an autosomal recessive genetic disorder and leads to alterations in the synthesis or function of the protein CFTR (cystic fibrosis transmembrane conductance regulator), resulting in the increased viscosity of secretions and therefore a progressive loss of pulmonary function, pancreatic function and other organs in which the expression of CFTR protein is involved. This objective: to evaluate the profile of 125 patients diagnosed with Cystic Fibrosis, children and adults treated in Espírito Santo State, Brazil. This Methods is Epidemiological study, observational, descriptive, transversal and reproductive. Patients had been treated at two hospitals (Hospital Infantil Nossa Senhora da Glória and Hospital Dório Silva) in Espírito Santo State between 1 January 2015 until 31 December 2015. Sociodemographics, clinical and laboratory data have been analysed. The analysis involved 87 children and 38 adults with their ages ranging from 2 to 80 years old and the median age of 14 years, 56% were male and the diagnosis of Cystic Fibrosis ranged from first month of life until 73 years old. SPSS for Windows, version 23.0, was used as a statistical analysis tool, significance level has been set to p<0.05 and confidence interval of 95%. The average dosage of chloride in sweat was 95,58 mEq/L and the average fecal elastase was 201.9 mg/g of faeces, with the paediatric group average being 167mEq/L. The Malnutrition was observed in 33 patients and respiratory symptoms was present in 80.8%. Staphylococcus aureus was mainly found in the pediatric age group and Pseudomonas aeruginosa in adults. Alfadornase was prescribed to 84.8% of the patients while enzymes were prescribed to 68% of the patients. Chloride dosage present in sweat has shown an inversely proportional relationship with the laboratory values of fecal elastase (p<0.001) and directly proportional with the diagnosis age of two years or youngers (p<0.001) and the radiological variable of the Shwachman Kulczycki score. However, it has not shown significance in relation to the mutations of the gene CFTR Delta-F508 (p=0.585). The fecal elastase has also presented statistical significance in relation to the diagnosis age of 2 years or older (p<0.001). Using 90 mgEq/L as the threshold point for the chloride, the obtained area under the ROC curve was 0.748 (p<0.001), sensibility 67,3% and specificity 38.6%. The high dosage of chloride in the sweat can be an indicative of higher risk of pancreatic insufficiency and should be investigated early by the health professional, enabling replacement of specific enzymes, can improve the quality of life and avoid complications of Cystic Fibrosis. Further research is required to confirm this correlation between the dosage of chloride in the sweat and fecal elastase.